(untitled) (MAUSAM, 2026)
We applied inverse probability weighting (IPW) causal modeling with multiple air pollutants (PM2.5, O3, and NO2), meteorological parameters, and potential lag effect of exposures to estimate the marginal effect of short-term exposure to air pollution (AP) on cause-specific mortality risks in the Indo-Gangetic Plain (IGP). A causal linkage between short-term exposure to PM2.5 and O3 was found with all four assessed causes of deaths (viz. neurological, respiratory, cardiovascular, and nephrological deaths), whereas NO2 was found to have a linkage only with the cardiovascular mortality risks; for every 10-ppb increase in NO2 exposure, the mean risk increased by 0.84percent (95percent Uncertainty interval (UI) = 0.58, 1.10). For every 10 microg m-3 increase in short-term PM2.5 exposure, the increase in the risk of in-hospital all-cause deaths, neurological deaths, respiratory deaths, cardiovascular deaths, and nephrological deaths was 1.76percent (1.57, 1.95), 0.28percent (0.07, 0.50), 0.73percent (0.47, 0.98), 0.72percent (0.48, 0.96), and 0.11percent (0.09, 0.14), respectively. Likewise, after controlling PM2.5 and NO2, the causation between acute exposure to O3 and respiratory mortality risk was found to be highest among all scenarios studied; for every 10-ppb increase in O3 there was a 2.24percent increase in the respiratory death risk (2.02, 2.45). This set of results from IPW causal modeling could serve as the causational evidence documenting relative risk (RR) estimates of premature cause-specific mortalities attributable to ambient AP in a subset of Indian population.